1974
DOI: 10.1139/o74-131
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Biosynthetic Difference between Isolated Mitochondria and Microsomes from Guinea-Pig and Rat Liver Regarding Lysophospharidic Acid, Phosphatidic Acid, CDP-Diglyceride, Phosphatidylglycerol, and Cardiolipin

Abstract: The enzymatic activities of marker enzymes (NADPH – cytochrome c reductase and glucose-6-phosphatase) and synthetic enzymes (acyl-CoA:sn-glycero-3-phosphate acyltransferase, CTP:sn-3-phosphatidic acid cytidyltransferase, and CDP-diglyceride:sn-glycero-3-phosphate phosphatidyltransferase) were measured in both isolated mitochondria and microsomes from liver of guinea pig and rat. Results thus obtained show a significant difference in activities of these enzymes between subcellular particles within species and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1976
1976
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Whether this variation results from species' differences or from different experimental conditions (no absolute dependence on CBPdig was established by Hostetler and Van Den Bosch 1972) remains to be determined. With respect to the differences between species, we demonstrated that the acylation of sn-glycero-3-phosphate to yield lyso-PtdA and PtdA in mitochondria isolated from guinea pig liver can be attributed to microsomal contamination, while in mitochondria isolated from rat liver the same acylation appears to be an intrinsic property of the mitochondrial membrane (Davidson and Stanacev 1974). Finally, this study has established that the biosynthesis of PtdGP and PtdG in submitochondrial membranes absolutely depends on CDP-dig.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Whether this variation results from species' differences or from different experimental conditions (no absolute dependence on CBPdig was established by Hostetler and Van Den Bosch 1972) remains to be determined. With respect to the differences between species, we demonstrated that the acylation of sn-glycero-3-phosphate to yield lyso-PtdA and PtdA in mitochondria isolated from guinea pig liver can be attributed to microsomal contamination, while in mitochondria isolated from rat liver the same acylation appears to be an intrinsic property of the mitochondrial membrane (Davidson and Stanacev 1974). Finally, this study has established that the biosynthesis of PtdGP and PtdG in submitochondrial membranes absolutely depends on CDP-dig.…”
mentioning
confidence: 67%
“…Our previous studies showed that the mitochondrial biosynthesis of CBP-dig can be attributed to microsomal contamination (Davidson andStanacev 1972, 1974) and that the transfer of CDP-dig from microsomal to mitochondrial membranes, isolated from guinea pig liver, can take place (Stuhne-Sekalec et 01. 1986).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low fatty acyd desaturase activity in the mitochondrial fraction may be due to contamination by microsomes. Hence, it seems likely that the higher specificity of CL synthesizing enzyme system to the molecular species containing 16:1 (Lt9) and 18:1 (Ltll) may be a cause for high contents of 16: 1 (Lt9) and 18: 1 (Ltll) in CL.…”
Section: Resultsmentioning
confidence: 99%